Omental sclerosing extramedullary hematopoietic tumors in Janus kinase-2 negative myelofibrosis: Caveat at frozen section - Sweety V Shinde; Asha S Shenoy; Dharmesh J Balsarkar; Vinaya B Shah (Wolters Kluwer Medknow Publications, 2014)
Sclerosing extramedullary hematopoietic tumors (SEMHTs) are associated with chronic myeloproliferative neoplasms. These extremely rare mass lesions were first described in kidney and peritoneum. On histopathology, they are characterized by sclerosis, entrapped fat, atypical megakaryocytes with myeloid and erythroid elements. Only approximately ten cases have been subsequently reported in orbit, lacrimal system, liver, omentum, and skin. The authors present a case of SEMHTs as incidentally detected omental nodules, while the patient was undergoing splenectomy for Janus kinase-2 negative myelofibrosis. The authors postulate their origin in omentum-associated lymphoid tissue; and highlight the diagnostic dilemma presented by SEMHTs at frozen section.